Macular thickness in healthy eyes of adults (N=4508) and relation to sex, age and refraction: The Tromsø Eye Study (2007-08) - Hanno, Therese von; Lade, Anette Caroline; Mathiesen, Ellisiv B.; Peto, Tunde; Njølstad, Inger; Bertelsen, Geir (Acta Ophthalmologica, 2016)
Published version. Source at http://dx.doi.org/10.1111/aos.13337 Purpose: To provide sex-stratified normative data on retinal thickness and study the relationship with sex, age and refractive status. Methods: Population-based study including 2617 women and 1891 men, aged 38– 87 (mean 61 8) years, without diabetes, glaucoma and retinal diseases, and spherical equivalent refraction (SER) within 6 dioptres. Retinal thickness was measured with optical coherence tomography (spectral domain Cirrus HD-OCT). Results: Women had thinner retina than men. Retinal thickness was significantly associated with refraction, where mean change in retinal thickness per 1Dincrease in SER was 1.3 (0.2) lm in the fovea, 0.7 (0.1) lm in the pericentral ring and 1.4 (0.1) lm in the peripheral ring. In the fovea, there was a non-monotonic curved relationship between retinal thickness and age in both sexes with a maximum at about 60 years (p < 0.001). In the pericentral ring, the mean reduction in retinal thickness per 10-year increase was 2.7 (0.3) lm in women and 4.0 (0.4) lm in men and corresponding results in the peripheral ring were 2.3 (0.3) lmin women and 2.6 (0.4) lmin men. In both regions, there was evidence for a nonlinear pattern with an increased rate of change with higher age. There was a significant interaction between sex and age for retinal thickness of the pericentral ring (p = 0.041). Conclusion: Women had thinner retina than men, and thickness varied with refractive status. Retinal thickness was associated with age in all macular regions, and the rate of change in retinal thickness varied at different ages.